PENGARUH KUALITAS PELAYANAN, KERAGAMAN PRODUK DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN DI TOKO WIDIA COLLECTION BALI - ASTANA, I GUSTI MADE OKA; MAHARANI, DESAK PUTU SEPTI YUNI (Universitas Mahasaraswati K. Mataram, 2024)
This study aims to gather information on the impact of Service Quality, Product Diversity, and Promotion on Purchase Decisions at Widia Collection Store Bali. The study population includes all customers, both men and women, who shop at Widia Collection Store Bali, with a sample size of 80 people. Data collection was conducted using the SPSS Version 25.00 for Windows application. The results of the study indicate that Service Quality has a positive effect on Purchase Decisions at Widia Collection Store Bali, with a t-value greater than the t-table value (3.551 > 1.667) and a significance level of 0.001 < 0.05. Product Diversity also has a positive effect on Purchase Decisions, with a t-value greater than the t-table value (2.349 > 1.667) and a significance level of 0.021 < 0.05. Additionally, Promotion has a positive effect on Purchase Decisions at Widia Collection Store Bali, with a t-value greater than the t-table value (2.641 > 1.667) and a significance level of 0.010 < 0.05.